A Potential Treatment of Non-Alcoholic Fatty Liver Disease with SIRT1 Activators - (:unkn) unknown (My University, 2014)
Sirtuins (SIRTs) are members of the silent information regulator-2 family and act as nicotinamide adenine dinucleotide (NAD+)-dependent histone/protein deacetylases. The de-acetylation of proteins and histones results in an up- or down-regulation of gene transcription and protein function. In recent years, the regulatory action of the deacetylation activity of SIRT1 has been shown to have a positive impact on the pathophysiological mechanisms of nonalcoholic fatty liver disease (NAFLD). Among the effects of SIRT1 are: its healing activity on insulin sensitivity, thereby ameliorating glycemic regulation; its mimetic activity on calorie restriction; its antihyperlipidemic activity on lipid homeostasis via the liver, adipose tissues and skeletal muscles; its anti-inflammatory activities; its protective effects against cardiovascular events and endothelial dysfunction; its positive influence on autophagy, apoptosis and cancer; and finally, its anti-aging activity. The current approach for the treatment of NAFLD involves the treatment of etiological factors and recommendation of life-style changes including more physical activity and a low-calorie diet. However, there is no specific medical treatments for NAFLD. The therapeutic potential of SIRT1 activity in the treatment of NAFLD discovered in humans has been presented in this article. In this review, the potential effects of SIRT1 activation on NAFLD-related pathophysiological mechanisms and on the treatment of NAFLD are discussed.
Keywords: Humans; Animals; Drug Design; Antioxidants; Oxidative Stress; Energy Metabolism; Liver; Signal Transduction; Enzyme Activation; Non-alcoholic Fatty Liver Disease; Anti-Inflammatory Agents; Molecular Targeted Therapy; Enzyme Activators; Sirtuin 1